Emerging nanobiomaterials against bacterial infections in postantibiotic era. Issue 3 (8th August 2020) - Hu, Dengfeng; Zou, Lingyun; Gao, Yifan; Jin, Qiao; Ji, Jian
Abstract: Although numerous antibiotics have been developed and applied in clinic, bacterial infections are still serious threats to human health, due to the rapidly growing antibiotic resistance all over the world. The causes of antibiotic resistance include two main aspects: the formation of bacterial biofilms and the self‐evolution of bacteria under the antibiotic selection pressure. It is of great significance to develop effective strategies to treat the bacterial infections with serious antibiotic resistance. With excellent performance, such as size effect, specific physicochemical property, easy modification, and so on, nanomaterials exhibit enormous potential as enhancers or therapeutic agents to treat severe drug‐resistant bacterial infections. In this review, the underlying causes for the antibiotic resistance are fully summarized and discussed. Subsequently, the promising therapeutic methods by using nanomaterials are provided and discussed to treat bacterial infections with serious antibiotic resistance. Abstract : Nanomaterials, with outstanding performance including size effect, specific physicochemical property, and easy modification, show immense potential as enhancers or therapeutic agents to treat bacterial infections with antibiotic resistance. In this review, the authors have summarized the underlying causes of antibiotic resistance. Subsequently, the promising therapeutic strategies by using nanomaterials to treat bacterial infections with severe antibiotic resistance are summarized and discussed.